5/4:4+7/9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\dfrac{5}{7}\times\dfrac{5}{9}+\dfrac{4}{9}\times\dfrac{5}{7}\)
\(=\dfrac{5}{7}\times\left(\dfrac{4}{9}+\dfrac{5}{9}\right)\)
\(=\dfrac{5}{7}\times1\)
\(=\dfrac{5}{7}\)
b) \(\dfrac{1}{10}+\dfrac{5}{9}+\dfrac{4}{9}+\dfrac{9}{10}-1\)
\(=\left(\dfrac{5}{9}+\dfrac{4}{9}\right)+\left(\dfrac{1}{10}+\dfrac{9}{10}-1\right)\)
\(=1+0\)
\(=1\)
c) \(\dfrac{5}{7}\times\dfrac{5}{9}+\dfrac{4}{9}\times\dfrac{5}{7}+\dfrac{2}{7}\)
\(=\dfrac{5}{7}\times\left(\dfrac{5}{9}+\dfrac{4}{9}\right)+\dfrac{2}{7}\)
\(=\dfrac{5}{7}+\dfrac{2}{7}\)
\(=1\)
d) \(\dfrac{2}{7}+\dfrac{2}{8}+\dfrac{1}{4}+\dfrac{1}{7}+\dfrac{4}{7}\)
\(=\left(\dfrac{2}{8}+\dfrac{1}{4}\right)+\left(\dfrac{2}{7}+\dfrac{1}{7}+\dfrac{4}{7}\right)\)
\(=\left(\dfrac{1}{4}+\dfrac{1}{4}\right)+1\)
\(=\dfrac{1}{2}+1\)
\(=\dfrac{3}{2}\)
e) \(\dfrac{4}{5}+\dfrac{3}{10}+\dfrac{2}{10}+0,7\)
\(=\dfrac{4}{5}+\dfrac{5}{10}+\dfrac{7}{10}\)
\(=\dfrac{4}{5}+\dfrac{12}{10}\)
\(=\dfrac{4}{5}+\dfrac{6}{5}\)
\(=\dfrac{10}{5}\)
\(=2\)
g) \(362\times728+326\times272\)
\(=326\times\left(728+272\right)\)
\(=326\times1000\)
\(=326000\)
\(9+2+5+3+7+8+4+2+9+6+4+65+6+7+4+6+3+7+4+8+5+9+08+87+1+2+3+4+2+3+2+5+6+767+5+75+6+4+6+5+66+5+7+546+46+43+6+3+6+4+6+7+8878+68+68+6+7+9+9=10961\)
\(\dfrac{8}{9}+\dfrac{3}{18}=\dfrac{16}{18}+\dfrac{3}{18}=\dfrac{19}{18}\) \(\dfrac{5}{7}-\dfrac{4}{11}=\dfrac{55}{77}-\dfrac{28}{77}=\dfrac{3}{11}\)
\(\dfrac{3}{4}+\dfrac{4}{5}=\dfrac{15}{20}+\dfrac{16}{20}=\dfrac{21}{20}\) \(\dfrac{5}{7}-\dfrac{3}{5}=\dfrac{25}{35}-\dfrac{21}{35}=\dfrac{4}{35}\)
\(\dfrac{7}{9}X\dfrac{3}{4}=\dfrac{7}{9}X\dfrac{3}{4}=\dfrac{7}{12}\) \(\dfrac{8}{3}X\dfrac{21}{4}=\dfrac{8}{3}X\dfrac{21}{4}=14\)
\(\dfrac{12}{7}:\dfrac{1}{4}=\dfrac{12}{7}X\dfrac{4}{1}=\dfrac{48}{7}\) \(\dfrac{7}{2}:\dfrac{9}{4}=\dfrac{7}{2}X\dfrac{4}{9}=\dfrac{14}{9}\)
3 × 4 = 12 | 2 × 6 = 12 | 4 × 3 = 12 | 5 × 6 = 30 |
3 × 7 = 21 | 2 × 8 = 16 | 4 × 7 = 28 | 5 × 4 = 20 |
3 × 5 = 15 | 2 × 4 = 8 | 4 × 9 = 36 | 5 × 7 = 35 |
3 × 8 = 24 | 2 × 9 = 18 | 4 × 4 = 16 | 5 × 9 = 45 |
Lời giải chi tiết:
2 = 1 + 1 |
6 = 2 + 4 |
8 = 5 + 3 |
10 = 8 + 2 |
3 = 1 + 2 |
6 = 3 + 3 |
8 = 4 + 4 |
10 = 7 + 3 |
4 = 3 + 1 |
7 = 6 + 1 |
9 = 8 + 1 |
10 = 6 + 4 |
4 = 2 + 2 |
7 = 5 + 2 |
9 = 7 + 2 |
10 = 5 + 5 |
5 = 4 + 1 |
7 = 4 + 3 |
9 = 6 + 3 |
10 = 10 + 0 |
5 = 3 + 2 |
8 = 7 + 1 |
9 = 5+ 4 |
10 = 0 + 10 |
6 = 5 + 1 |
8 = 6 + 2 |
10 = 9 + 1 |
1 = 0 + 1 |
2=1+1 6=2+4 8=5+3 10=8+2
3=1+2 6=3+3 8=4+4 10=7+3
4=3+1 7=6+1 9=8+1 10=6+4
4=2+2 7=5+2 9=7=2 10=5+5
5=4+1 7=4+3 9=6+3 10=10+0
5=3+2 8=7+1 9=5=4 10=0+10
6=5+1 8=6=2 10=9+1 1=0+1
a) \(\left(\dfrac{3}{29}-\dfrac{1}{5}\right)\cdot\dfrac{29}{3}\)
\(=\dfrac{3}{29}\cdot\dfrac{29}{3}-\dfrac{1}{5}\cdot\dfrac{29}{3}\)
\(=1-\dfrac{29}{15}\)
\(=\dfrac{15-29}{15}\)
\(=-\dfrac{14}{15}\)
b) \(\dfrac{3}{4}\cdot\dfrac{7}{9}+\dfrac{1}{4}\cdot\dfrac{7}{9}\)
\(=\dfrac{7}{9}\cdot\left(\dfrac{1}{4}+\dfrac{3}{4}\right)\)
\(=\dfrac{7}{9}\cdot1\)
\(=\dfrac{7}{9}\)
c) \(\dfrac{1}{7}\cdot\dfrac{5}{9}+\dfrac{5}{9}\cdot\dfrac{1}{7}+\dfrac{5}{9}\cdot\dfrac{3}{7}\)
\(=\dfrac{5}{9}\cdot\left(\dfrac{1}{7}+\dfrac{1}{7}+\dfrac{3}{7}\right)\)
\(=\dfrac{5}{9}\cdot\dfrac{5}{7}\)
\(=\dfrac{25}{63}\)
d) \(4\cdot11\cdot\dfrac{3}{4}\cdot\dfrac{9}{121}\)
\(=\left(4\cdot\dfrac{3}{4}\right)\cdot\left(11\cdot\dfrac{9}{121}\right)\)
\(=3\cdot\dfrac{9}{11}\)
\(=\dfrac{27}{11}\)
1) Ta có: \(\frac{-4}{7}-\frac{11}{19}+\frac{13}{19}\cdot\frac{-3}{7}+\frac{2}{19}:\frac{-7}{4}\)
\(=\frac{-4}{7}-\frac{11}{19}-\frac{39}{133}-\frac{8}{133}\)
\(=\frac{-76}{133}-\frac{77}{133}-\frac{39}{133}-\frac{8}{133}\)
\(=\frac{-200}{133}\)
2) Ta có: \(\left(\frac{-4}{9}+\frac{3}{5}\right):\frac{1}{\frac{1}{5}}+\left(\frac{1}{5}-\frac{5}{9}\right):\frac{1}{\frac{1}{5}}\)
\(=\left(\frac{-4}{9}+\frac{3}{5}\right)\cdot\frac{1}{5}+\left(\frac{1}{5}-\frac{5}{9}\right)\cdot\frac{1}{5}\)
\(=\frac{1}{5}\left(\frac{-4}{9}+\frac{3}{5}+\frac{1}{5}-\frac{5}{9}\right)\)
\(=\frac{1}{5}\left(-1+\frac{4}{5}\right)\)
\(=\frac{1}{5}\cdot\frac{-1}{5}=\frac{-1}{25}\)
3) Ta có: \(\frac{4}{5}-\left(-\frac{2}{7}\right)-\frac{7}{10}\)
\(=\frac{4}{5}+\frac{2}{7}-\frac{7}{10}\)
\(=\frac{56}{70}+\frac{20}{70}-\frac{49}{70}\)
\(=\frac{27}{70}\)
4) Ta có: \(\frac{2}{7}-\left(-\frac{13}{15}+\frac{4}{9}\right)-\left(\frac{5}{9}-\frac{2}{15}\right)\)
\(=\frac{2}{7}+\frac{13}{15}-\frac{4}{9}-\frac{5}{9}+\frac{2}{15}\)
\(=\frac{2}{7}+1-1=\frac{2}{7}\)
\(\dfrac{5}{4}\): 4 + \(\dfrac{7}{9}\)
= \(\dfrac{5}{4}\) \(\times\) \(\dfrac{1}{4}\) + \(\dfrac{7}{9}\)
= \(\dfrac{5}{16}\) + \(\dfrac{7}{9}\)
= \(\dfrac{45}{144}\) + \(\dfrac{112}{144}\)
= \(\dfrac{157}{144}\)